Pemanfaatan Aplikasi Google Classroom dan Video Pembelajaran Sebagai Media Belajar Dalam Upaya Meningkatkan Motivasi Siswa Sekolah Dasar di Masa Pandemi Covid-19 - Jasmine, Sophia; Irawati, Riana; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2021)
The existence of the COVID-19 pandemic virus in Indonesia has caused all activities to be carried out from home. In order to reduce the spread of the COVID-19 pandemic, the government changed the education system to be bold. So that in the world of education all teachers must be able to create learning media that can be operated effectively by students from home. This research was carried out using a qualitative research methodology with a descriptive method, the aim of this research is to find out the benefits of the google classroom application and learning videos as learning media in an effort to increase student learning motivation during the Covid-19 pandemic. Based on the results of the study by referring to relevant journals and articles, it was stated that the use of the google classroom application and video learning as a learning medium had a positive effect of 86.30% in increasing students' learning motivation at Tarumajaya 2 Elementary School. So it can be said that the use of google classroom and video learning at Tarumajaya 2 Elementary School is going well.